2016
DOI: 10.11152/mu.2013.2066.183.qia
|View full text |Cite
|
Sign up to set email alerts
|

Layer-specific myocardial strain analysis: investigation of regional deformation in a rabbit model of diabetes mellitus during different stages.

Abstract: Aim: The purpose of the present study was to determine the characteristics of myocardial damage at different stages of diabetes mellitus (DM) using layer-specific myocardial strain. Material and methods: Thirty six New Zealand white rabbits were randomly divided into either the control group (n =18) or the DM group (induced with alloxan) (n=18). For the myocardial deformation studies echocardiography and layer-specific strain were performed at baseline and after 3, 6, and 9 months in all of the rabbits. Three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…30 In patients with ischemia, not only the endocardial CS but also epicardial CS decreases as the disease progresses. 19, 27 Furthermore, we previously reported on the time course of LV dysfunction in patients with repaired tetralogy of Fallot: impaired myocardial deformation increases with age, extending from the endocardium to the epicardium.…”
Section: Relationship With Cumulative Anthracycline Dosementioning
confidence: 99%
“…30 In patients with ischemia, not only the endocardial CS but also epicardial CS decreases as the disease progresses. 19, 27 Furthermore, we previously reported on the time course of LV dysfunction in patients with repaired tetralogy of Fallot: impaired myocardial deformation increases with age, extending from the endocardium to the epicardium.…”
Section: Relationship With Cumulative Anthracycline Dosementioning
confidence: 99%
“…16 Yu et al showed that in anthracycline-treated survivors of childhood cancers, subendocardial circumferential deformation is sensitive to anthracycline. 17 In a rabbit model of DM, 25 and in patients with ischemia 15 or hypertension, 26 the vulnerability of the endocardial layers has been proposed. Although vulnerability of the endocardial layers in patients with rTOF has not been clarified physiologically or pathologically, the present study's findings demonstrated that potential myocardial damage occurs in the endocardial layers before the midmyocardial and epicardial layers in patients with rTOF when measured with layer-specific strain analysis, which is concordant with findings in reports on other diseases.…”
Section: Rotation and Torsional Behaviormentioning
confidence: 99%
“…15,16 Studies of animal models of T1DM have also demonstrated LV dysfunction. [6][7][8] Some studies indicated that cardiac dysfunction begins during childhood or adolescence, 9,17,18 but the long-term changes of DCM in patients with T1DM, especially between childhood and adulthood, remain unknown.…”
Section: Study Populationmentioning
confidence: 99%
“…4 Although ischemic heart disease has been the most researched form of CVD in patients with T1DM, 4 diabetic cardiomyopathy (DCM) has recently attracted a great deal of attention. [5][6][7][8][9] DCM is defined as myocardial dysfunction independent of coronary artery disease and hypertension. 10 The development of DCM is associated with structural and functional alterations in cardiomyocytes, coronary microangiopathy, Layer-Specific Strain Analysis in T1DM Patients…”
mentioning
confidence: 99%